2020
DOI: 10.3389/fimmu.2020.01609
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Histone Deacetylases in Human Macrophages Promotes Glycolysis, IL-1β, and T Helper Cell Responses to Mycobacterium tuberculosis

Abstract: Tuberculosis (TB) is the leading infectious killer in the world. Mycobacterium tuberculosis (Mtb), the bacteria that causes the disease, is phagocytosed by alveolar macrophages (AM) and infiltrating monocyte-derived macrophages (MDM) in the lung. Infected macrophages then upregulate effector functions through epigenetic modifications to make DNA accessible for transcription. The metabolic switch to glycolysis and the production of proinflammatory cytokines are key effector functions, gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 75 publications
3
41
0
Order By: Relevance
“…Newborn babies are more susceptible than adults to a variety of bacterial infections, including from gram negative organisms (containing LPS) and from intracellular pathogens such as Mycobacterium tuberculosis (Mtb) (15,16), the causative agent of Tuberculosis (TB). Our laboratory has previously shown that adult human macrophages shift their metabolic function toward aerobic glycolysis after Mtb infection (17)(18)(19), a finding replicated in other centres (20,21). Furthermore, research examining monocytes and MDM from umbilical cord blood have shown them to be functionally impaired in relation to adult comparators, although the data can be contradictory (22)(23)(24).…”
Section: Introductionmentioning
confidence: 80%
“…Newborn babies are more susceptible than adults to a variety of bacterial infections, including from gram negative organisms (containing LPS) and from intracellular pathogens such as Mycobacterium tuberculosis (Mtb) (15,16), the causative agent of Tuberculosis (TB). Our laboratory has previously shown that adult human macrophages shift their metabolic function toward aerobic glycolysis after Mtb infection (17)(18)(19), a finding replicated in other centres (20,21). Furthermore, research examining monocytes and MDM from umbilical cord blood have shown them to be functionally impaired in relation to adult comparators, although the data can be contradictory (22)(23)(24).…”
Section: Introductionmentioning
confidence: 80%
“…This process, also termed the “Warburg Effect”, involves a shift in cellular energy metabolism to increased glycolysis and reduced oxidative phosphorylation, thereby causing TCA cycle intermediates to accumulate (25). Indeed, in vitro studies of human pulmonary macrophages show the ability of Mtb to induce aerobic glycolysis is necessary to stimulate production of IL-1β (23, 26).…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the epigenetic mechanisms involved in chronic diseases and infections can be critical not only to understand the pathogenesis mechanisms of these diseases but also to design novel therapeutic interventions. For instance, in tuberculosis, the inhibition of HDACs using suberanilohydroxamic acid (SAHA), also known as the drug Vorinostat, resulted in an immune response by macrophages and subsequently T cells against Mtb [ 86 ]. This immune response involved increased production of IL-1β and reduction of IL-10, accompanied by stimulation of T cells in a human Mtb-infected macrophage culture system [ 86 ].…”
Section: Pharmacologically Induced Epigenetic Control Of Mmpsmentioning
confidence: 99%
“…For instance, in tuberculosis, the inhibition of HDACs using suberanilohydroxamic acid (SAHA), also known as the drug Vorinostat, resulted in an immune response by macrophages and subsequently T cells against Mtb [ 86 ]. This immune response involved increased production of IL-1β and reduction of IL-10, accompanied by stimulation of T cells in a human Mtb-infected macrophage culture system [ 86 ]. Furthermore, in water-borne parasitic infections by Cryptosporidium species (causing cryptosporidiosis) such as C. parvum, Vorinostat showed anti-parasitic in vitro and in vivo potential by targeting the HDAC of C. parvum [ 87 ].…”
Section: Pharmacologically Induced Epigenetic Control Of Mmpsmentioning
confidence: 99%